Implementation of Peace Culture in Instilling Tolerance and Moderate Attitudes at Hubbul Qur'an Islamic Boarding School in Nogosari Village Rambipuji District Jember Regency - Al ubaidy, Miftahus Sa'diyah; Mukit, Abd; Al Asy ari, M. Khoirul Hadi (Islamic Insights Journal, 2019)
Lately, there have often been situations of differences and debates that have occurred among the community such as violence and riots which have resulted in the birth of hatred for each other. Meanwhile on May 13, 2018 the involvement of children and women in suicide bombings in Surabaya gave birth to the assumption of women based on religion-based radicalism that could divide the peace and Student of the Jember State Islamic Institute (IAIN)schools are expected to become the main container and become a model for the community in tackling such situations and can instill values of tolerance and peace. The focus of this research is how to implement a culture of peace in pesantren in instilling tolerance and moderation. This research method uses a qualitative descriptive approach with interview and observation techniques. The results of this study indicate that the Hubbul Qur'aan Islamic boarding school in Nogosari Village promotes a pluralist attitude, tolerance to local culture and acceptance of social development.Keywords: Implementation, Peace Culture, Tolerance and Moderate Attitude.